(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper attempts to highlight the horrible political conditions existing in India at the time of the reign of Mrs. Indira Gandhi. Representation of contemporary politics has been a major theme for Contemporary Indian Writing in English. A number of eminent novelists such as Rohinton Mistry, Salman Rushdie, Vikram Seth, Shashi Tharoor, Amitav Ghosh, Khushwant Singh, Nayantara Sahgal and Kiran Desai have tried to bring the hidden truth and facts on the surface by the representation of contemporary politics. In their writings, the novelists blend facts and fiction to recreate and re-examine the earlier happenings, events, views and assumptions. The main objective of Rohinton Mistry is to show how politics is used to manipulate the common masses to just safeguard their vested interests to remain in power.